LABORATORY DIAGNOSTICS OF AUTOIMMUNE DISEASES - Akhmedova Sarvinoz (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Autoimmune diseases are a broad group of pathologies that arise due to the immune system attacking the cells of its own body. In other words, in such diseases, the human immune system perceives the cells of its own body as foreign agents and produces antibodies to them, thus damaging tissues [1,2].